Research on Safety Early Warning Standard of Large-Scale Underground Utility Tunnel in Ground Fissure Active Period - Wang, X. Y.; Ma, Z.; Zhang, Y. T. (Frontiers in Earth Science, 2022)
Safety control of large-scale underground utility tunnels is vital for engineering management units. The establishment of early warning indicator systems and standards is critical for safety control. However, there is limited related research for engineering construction, operation, and maintenance management. Numerical analysis results of the mechanical response of the underground utility tunnel of the Xi'an Xingfu LinDai project (the largest underground urban complex in Asia) at different intersection angles and ground fissure displacements were obtained. The vertical surface settlement, structural stress, fissure displacement, and contact pressure are proposed as early warning indicators of the structure of the underground utility tunnel during the active period of a ground fissure. The safety control values and early warning standards are given based on the analysis of the results. The safety warning indicator system and standards proposed in this article are concise, practical, and easy to implement. The data sample required by this warning indicator system is small and can be obtained using conventional monitoring sensors, which can be referenced for similar projects.